Solitary fibrous tumor/hemangiopericytoma in the cerebellopontine angle mimicking vestibular schwannoma: A case report and literature review - Yue, Xi (Medicine (Baltimore), 2020)
RATIONALE: Intracranial solitary fibrous tumors (SFTs) and hemangiopericytomas (HPCs) are rare spindle cell tumors of mesenchymal origin that include benign and malignant neoplasms. PATIENT CONCERNS: We present a 66-year-old male with a 5-year history of headache and dizziness, with left progressive sensorineural hearing loss over 1 month. DIAGNOSES: WHO grade II SFT/HPC originating from the internal auditory canal in the left cerebellopontine angle. INTERVENTIONS: surgical resection. OUTCOMES: No local recurrence or metastases were observed in the follow-up 3 months after the surgery. LESSONS: Intracranial SFTs/HPCs are rare mesenchymal neoplasms that are challenging to manage. If the imaging characteristics of tumor are not typical, clinicians should depend on tissue biopsy and immunohistochemistry to make a definitive diagnosis.